Efektivitas High Intensity Interval Training (HIIT) dan Sprint Interval Training (SIT) dalam Meningkatkan Kapasitas Aerobik (VO₂Max) Atlet Sepak Bola - Isnaeni Nur Maulida Putri; -, Sugiono; Nitaya Putri Nur Hidayati (Jurusan Fisioterapi Poltekkes Kemenkes Surakarta, 2026)
Background: VO₂max is the gold standard for measuring aerobic fitness and plays an important role in supporting the performance of soccer athletes during matches lasting 2 × 45 minutes. High Intensity Interval Training (HIIT) and Sprint Interval Training (SIT) are two types of interval training that are commonly used to improve VO₂max. Objective: This study aimed to determine the effectiveness of HIIT and SIT on increasing VO₂max in soccer athletes. Methods: This study used a two groups pre-test and post-test design. The research subjects were athletes from SSB AT-Farmasi Solo who met the inclusion and exclusion criteria. A total of 16 subjects were randomly divided into two groups, namely the HIIT group and the SIT group, with eight subjects in each group. The intervention was conducted in six training sessions over a period of two weeks with a frequency of three sessions per week. During the study, two subjects dropped out, leaving fourteen subjects for analysis. VO₂max was measured using the beep test. Data analysis was performed using the Wilcoxon test to determine differences before and after the intervention and the Mann–Whitney test to determine differences between groups. Results: (1) There was an increase in VO₂max in the HIIT group after the intervention with a p-value of 0.014 (p < 0.05); (2) There was an increase in VO₂max in the SIT group after the intervention with a p-value of 0.011 (p < 0.05); (3) There was no significant difference in the effect of HIIT and SIT on increasing VO₂max with a p-value of 0.53 (p > 0.05). Conclusion: (1) HIIT is effective in increasing VO₂max in soccer athletes; (2) SIT is effective in increasing VO₂max in soccer athletes; (3) There is no difference in the effect of HIIT and SIT on increasing VO₂max in soccer athletes.